2020
DOI: 10.3390/molecules25081922
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Cornelian Cherries on Lipid Profile and NO/ROS Balance in Obese Zucker Rats: Comparison with CoQ10

Abstract: Cornelian cherries (CCs) belong to promising anti-obesity substances. We aimed to study effects of coenzyme Q10 (CoQ10) and two varieties of CCs on lipid profile, ROS, and nitric oxide (NO) production in obese rats. Male Zucker rats were divided into the control group and groups treated with CoQ10 (30mg/kg/day), or CC varieties: Koralovij Marka (KM) and Wild Type (WT) (5 g/kg/day, n = 6 in each group) for 6 weeks. Blood pressure (BP), bodyweight, relative heart weight, and plasma lipid profile were determined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…One of diabetes symptoms is a decrease in body weight caused by insulin resistance and impairment in whole-body glucose uptake. Dayar et al [ 35 ] also observed non-significant impact of wild type Cornelian cherries administration (5 g/kg/day for six weeks) on the body weight in obese Zucker rats. Our study seems to be the first evaluating the effect of Cornelian cherry pulp on femoral weight and length.…”
Section: Discussionmentioning
confidence: 99%
“…One of diabetes symptoms is a decrease in body weight caused by insulin resistance and impairment in whole-body glucose uptake. Dayar et al [ 35 ] also observed non-significant impact of wild type Cornelian cherries administration (5 g/kg/day for six weeks) on the body weight in obese Zucker rats. Our study seems to be the first evaluating the effect of Cornelian cherry pulp on femoral weight and length.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 provides examples of these bioactive compounds along with their host foods [81][82][83][84][85][86][87]. The structural diversity between flavonoid subgroups produces different beneficial properties, such as antioxidant, anti-inflammatory, anti-diabetic, and/or antithrombotic activities [88][89][90][91]. In general, more than two-thirds of the polyphenols consumed in one's diet are flavonoids.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Furthermore, the cornelian cherry that contains a high amount of polyphenols has anti-atherosclerotic properties mainly based on its ability to curtail the inflammation process and improve endothelial dysfunction [ 59 ]. Dayar et al [ 156 ] documented that different types of cornelian cherries have better beneficial effects than the powerful antioxidant coenzyme Q10 in obese Zucker rats. In contrast to coenzyme Q10, cornelian cherries decreased cholesterol, LDL levels, and ROS production, while increasing eNOS activity/expression [ 156 ].…”
Section: Therapeutic Effects Of Polyphenols-loaded Polymeric Nanopmentioning
confidence: 99%
“…Dayar et al [ 156 ] documented that different types of cornelian cherries have better beneficial effects than the powerful antioxidant coenzyme Q10 in obese Zucker rats. In contrast to coenzyme Q10, cornelian cherries decreased cholesterol, LDL levels, and ROS production, while increasing eNOS activity/expression [ 156 ]. In a randomized controlled trial, Chai et al [ 157 ] showed that tart cherries can lower the systolic blood pressure and LDL cholesterol levels in older adults.…”
Section: Therapeutic Effects Of Polyphenols-loaded Polymeric Nanopmentioning
confidence: 99%